Modelling the Combined Use of Long-Lasting Insecticidal Nets and Insecticides Zooprophylaxis Against the Resilience of Anopheles Arabiensis for Effective Malaria Control - Levens, Watson (Tanzania Journal of Science, 2024)
Malaria is a significant public health concern, especially in tropical regions. It remains endemic in many areas where malaria mosquitoes are prevalent. This study investigates the viability of insecticide zooprophylaxis (IZ) in conjunction with Long Lasting Insecticidal Nets (LLINs) as a strategic approach to combat malaria transmission, particularly in regions dominated by zoophagic vectors. Through the presentation and analysis of a mathematical model that integrates IZ and LLINs for the control of Anopheles arabiensis (An. arabiensis), the research underscores IZ's role in reducing zoophagic vector populations and enhancing malaria control efforts. Notably, the study reveals that achieving comprehensive coverage of LLINs and IZ distribution systems can reduce the basic reproduction number (R₀) below 1. Furthermore, the research highlights the potential for substantial reductions in human biting rates, vectorial capacity and Entomological Inoculation Rate (EIR) when high intervention coverage encompasses all zoophagy blood sources for malaria vectors.